Penilaian Hasil Belajar dengan Kurikulum 2013 di SD Islam Alexandria Kota Tangerang - Asrifah, Diah Nur; Luthfiyah, Luthfiyah; Karunina, Melita; Rachmawati, Royyan Zam zam (Lembaga Yasin AlSys, 2022)
This study aims to describe the assessment of learning outcomes based on the implementation of the 2013 Curriculum. This research was conducted in Tangerang City, Banten Province in the academic year 2021-2022. The principals and teachers of the Islamic Elementary School of Alexandria were involved in this study. The data of this research were obtained from the interview process with the Principal and Teachers of the Islamic Elementary School of Alexandria. The results of this study indicate that the assessment area of the 2013 Curriculum is divided into 4 aspects of assessment, namely: student spirituality, student social, student knowledge and student skills. In determining the assessment of student learning outcomes, the teacher experienced several problems, both from students and the method applied. Based on these findings, it is suggested that the assessment of learning outcomes should be carried out in accordance with the principles of assessment.